1986
DOI: 10.1002/ajim.4700100108
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos dust exposure during brake repair

Abstract: About 10,000 tons of chrysotile per year are used in the Federal Republic of Germany for the production of friction materials. During brake repair an unknown number of approximately 300,000 mechanics in automobile service stations are exposed to asbestos dust. In a field study, asbestos fiber concentrations during brake repair were measured. Occupational histories and chest X-rays of brake service mechanics are being examined. Ninety dust measurements in 76 service stations were made by phase contrast microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 4 publications
3
41
1
Order By: Relevance
“…These authors found no statistically significant differences between 8-h TWA concentrations experienced by US versus Swedish brake mechanics (Plato study) in the late 1970s/ early 1980s time frame (such a comparison cannot be conducted for the Ro¨delsperger et al (1986) data, because data for individual mechanics were not provided.) Therefore, the lower cumulative lifetime exposure estimate for US brake mechanics is more likely to be attributable to shorter job tenure (as compared with European mechanics) than to differences in airborne chrysotile concentrations.…”
Section: Exposure Concentrationsmentioning
confidence: 97%
See 4 more Smart Citations
“…These authors found no statistically significant differences between 8-h TWA concentrations experienced by US versus Swedish brake mechanics (Plato study) in the late 1970s/ early 1980s time frame (such a comparison cannot be conducted for the Ro¨delsperger et al (1986) data, because data for individual mechanics were not provided.) Therefore, the lower cumulative lifetime exposure estimate for US brake mechanics is more likely to be attributable to shorter job tenure (as compared with European mechanics) than to differences in airborne chrysotile concentrations.…”
Section: Exposure Concentrationsmentioning
confidence: 97%
“…Plato et al (1995) estimated a mean annual asbestos concentration of 0.09 f/cm 3 (range, 0.01-0.46 f/cm 3 ) in car mechanics. Ro¨delsperger et al (1986) calculated mean exposure concentrations of car and truck mechanics as 0.04 and 0.08 f/cm 3 , respectively, based on a combination of activities. In the Gustavsson et al (1990) study, data from garages were used to estimate asbestos concentrations for three levels of exposure: 0.0, 0.08, and 0.16 f/cm 3 .…”
Section: Exposure Concentrationsmentioning
confidence: 99%
See 3 more Smart Citations